Comparison of Occipital Condyle Morphometry in Various Populations with Respect to Skull Base Surgery - Ramalingam, Sudha; Somanath, Deepa (Academia Anatomica International, 2017)
Background: The craniovertebral junction is made up of the occiput, upper two cervical vertebrae. Occipital condyle is one the landmarks on the skull base. Morphometric values of these condyles in a specific population is to be known by surgeons to deal with pathologies affecting the cranial base without disturbing the neurovascular structures by doing appropriate condylectomy and to ensure occipito-cervical fusion in case of instability. Methods: The study was performed by comparing the morphometric values of occipital condyles with other populations (Greek, Turkish, Korean, Chinese, American, European and Indian). The data regarding the morphometric values of occipital condyles was taken from our previously published article with a sample of hundred occipital condyles of unsexed dry human skulls of unknown age and compared with the studies of other population. The measurements compared were the length, breadth and thickness of the occipital condyle, intercondylar distance in anterior, middle and posterior parts of the occipital condyles, the angle of the occipital condyle to the sagittal plane and coronal planes and shape of the occipital condyles. Results: Most of the morphometric values of OC in South Indian were lesser than the other populations like breadth, thickness,anterior intercondylar distance, posterior intercondylar distance, angle of the occipital condyle to the sagittal plane. Conclusion: This information has to borne in mind while performing surgical procedures like occipito-cervical screw fixation, condylar drilling in cranial base surgery in South Indian population.